Radical Cartesianism : the French reception of Descartes - Schmaltz, Tad M., 1960- (Cambridge University Press, 2002)
This is the first book-length study of two of Descartes's most innovative successors, Desgabets and Regis, and of their highly original contributions to Cartesianism. The book establishes the important though neglected role played by Desgabets and Regis in the theologically and politically charged reception of Descartes in early-modern France.